Clinical meaning of serum trimethylamine oxide, N-terminal-pro-brain natriuretic peptide, hypoxia-inducible factor-1α and left ventricular function and pregnancy outcome in patients with pregnancy-induced hypertension - Liang, YunTai; Liang, YunTai; Wu, Yue; Duan, LiHong; Xiao, ChunHui; Ren, ZeYa (Journal of Medical Biochemistry, 2022)
Purpose: To figure out the clinical meaning of serum trimethylamine oxide (TMAO), N-terminal-pro-brain natriuretic peptide (NT-proBNP) and hypoxia-inducible factor-1α (HIF-1α) with left ventricular function and pregnancy outcome in patients with pregnancy-induced hypertension.Methods: From January 2018 to October 2020, taking 117 patients with gestational hypertension was as the research objects, assignation of them was into the gestational hypertension (pregnancy-induced hypertension group, 55 cases), mild preeclampsia (the mild PE, 43 cases) and severe preeclampsia (the severe PE, 19 cases) in the light of the severity of the disease. Analysis of the link of serum TMAO, NT-proBNP and HIF-1α with severity of disease and cardiac function indexes in patients with gestational hypertension was conducted; All patients were followed up to the end of pregnancy, and analysis of the predictive value of serum TMAO, NT-proBNP and HIF-1α on pregnancy outcome in patients was conducted.Results:  The serum TMAO and NT-proBNP of patients were elevated, while HIF-1α was reduced with the severity of the disease (P < 0.05). The serum TMAO, NT-proBNP in patients with gestational hypertension were positively linked, but HIF-1α was negatively correlated with the severity of the disease (P < 0.05).  Left ventricular end-diastolic volume (LVEDV) and left ventricular end-systolic volume (LVESV) were elevated in gestational hypertension patients, while ejection fraction (LVEF) was reduced with the severity of disease (P < 0.05). The serum TMAO, NT-probNP and HIF-1α were implicated in LVEDV, LVESV and LVEF values in patients with gestational hypertension (P < 0.05). The serum TMAO and NT-probNP in the poor pregnancy outcome were elevated vs. the good pregnancy outcome, but HIF-1α was reduced (P < 0.05). The AUC of the prediction of combined detection of serum TMAO, NT-probNP and HIF-1α on pregnancy outcome was greater vs. alone detection of each index (P < 0.05).Conclusion: Serum TMAO, NT-proBNP and HIF-1α in patients with gestational hypertension are linked with disease severity and cardiac function, and have predictive and evaluative values for disease severity and pregnancy outcome.